1999
DOI: 10.1109/50.774243
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk performance of integrated optical cross-connects

Abstract: Abstract-Crosstalk performance of monolithically integrated multiwavelength optical cross-connects (OXC's) depends strongly on their architecture. In this paper, a semiquantitative analysis of crosstalk in 11 different architectures is presented. Two architectures are analyzed numerically in more detail and the results of the analysis show good agreement with previously reported experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The present model can be expanded to account for (de)multiplexing crosstalk. However, it should be mentioned that integrated optical cross-connects can be designed in such a way that crosstalk caused by the switches becomes the dominant crosstalk contribution [4]. Because of reasons of limited computation time, higher order crosstalk accumulation is not taken into account.…”
Section: Conceptsmentioning
confidence: 99%
“…The present model can be expanded to account for (de)multiplexing crosstalk. However, it should be mentioned that integrated optical cross-connects can be designed in such a way that crosstalk caused by the switches becomes the dominant crosstalk contribution [4]. Because of reasons of limited computation time, higher order crosstalk accumulation is not taken into account.…”
Section: Conceptsmentioning
confidence: 99%
“…One advantage of configurations using one AWG only is that the channel wavelengths automatically fit. A comparison of crosstalk properties of different configurations is given in [21].…”
Section: Configuration-dependent Crosstalk In Add-drop Multiplexersmentioning
confidence: 99%
“…Although interferometric crosstalk can be treated in a general way [cf., (10)], we focus our analysis on the above described regime based on the assumption that future WDM networks will make use of OXC's with optimized crosstalk performance. For instance, it has been shown that in integrated OXC's the circuit configuration can be chosen such that the amount of crosstalk is minimized and that the dominant crosstalk contributions are in the incoherent regime [5], [9]. For the case considered here the autocorrelation function of interferometric crosstalk is given by (11) 2) Filtered Interferometric Crosstalk: At the output of the postdetection filter, , the filtered interferometric noise is denoted by (12) where represents the convolution operation.…”
Section: B Interferometric Crosstalkmentioning
confidence: 99%
“…8.3.2]) (8) where is found to be (9) Substitution of (9) in (8) yields (10) 1) Incoherent Interferometric Noise: We are interested in analyzing interferometric crosstalk arising from performance imperfections of optical cross connects (OXC) in WDM networks. We proceed by making the following assumptions.…”
Section: B Interferometric Crosstalkmentioning
confidence: 99%